Effect of UV-B radiation on amino acids profile, antioxidant enzymes and lipid peroxidation of some cyanobacteria and green algae. (1st September 2020) - Saber, Hani; El-Sheekh, Mostafa M.; Ibrahim, Aml; Alwaleed, Eman A.
Abstract: Background: UV radiation and its impact on living organisms became an essential concern over the past three decades and will be essential in the years to come. So, the present investigation was devoted to examining the impact of artificial UV-B radiation on the accumulation of amino acids and MDA contents as well as some antioxidant enzymes activities in three freshwater cyanobacterial species; Planktothrix cryptovaginata, Nostoc carneum and Microcystis aeruginosa, one freshwater green alga; Scenedesmus acutus and one marine cyanobacterium; Microcystis . Methods: The algal cultures were exposed directly to artificial UV-B radiation for 1, 3, 5, and 7 hours and amino acids, MDA contents, and the antioxidant enzyme activities; CAT, POD, APX, and SOD were analyzed. Results: The data obtained indicated that alteration in MDA and antioxidant enzymes by UV stress depends on the algal species and the exposure time. The treatment of the investigated algae with different periods of UV-B exposure stimulated the biosynthesis of some individual amino acids and inhibited the accumulation of some others. In some cases, exposure to UV-B was accompanied by the disappearance of some amino acids. In addition, UV-B exposure for 3 hours stimulated the accumulation of total amino acids in M. aeruginosa and S. acutus, while 7 hours of UV-B enhanced the biosynthesis of total amino acids in M. aeruginosa only from the investigated algae. Conclusion: Exposure of some cyanobacteria and green algae to UV-B radiation stimulated the biosynthesis of some individual amino acids and inhibited the accumulation or accompanied by the disappearance of some others. However, the alteration in MDA and antioxidant enzymes by UV stress depends on the algal species and the exposure time.